Positive peritoneal lavage fluid cytology based on isolation by size of epithelial tumor cells indicates a high risk of peritoneal metastasis - Xuan, Ying; Gao, Qizhong; Wang, Chenhu; Cai, Dongyan (PeerJ, 2024)
Background Peritoneal metastasis (PM) is the most prevalent type of metastasis in patients with gastric cancer (GC) and has an extremely poor prognosis. The detection of free cancer cells (FCCs) in the peritoneal cavity has been demonstrated to be one of the worst prognostic factors for GC. However, there is a lack of sensitive detection methods for FCCs in the peritoneal cavity. This study aimed to use a new peritoneal lavage fluid cytology examination to detect FCCs in patients with GC, and to explore its clinical significance on diagnosing of occult peritoneal metastasis (OPM) and prognosis. Methods Peritoneal lavage fluid from 50 patients with GC was obtained and processed via the isolation by size of epithelial tumor cells (ISET) method. Immunofluorescence and fluorescence in situ hybridization (FISH) were used to identify FCCs expressing chromosome 8 (CEP8), chromosome 17 (CEP17), and epithelial cell adhesion molecule (EpCAM). Results Using a combination of the ISET platform and immunofluorescence-FISH, the detection of FCCs was higher than that by light microscopy (24.0% vs. 2.0%). Samples were categorized into positive and negative groups, based on the expressions of CEP8, CEP17, and EpCAM. Statistically significant relationships were demonstrated between age (P = 0.029), sex (P = 0.002), lymphatic invasion (P = 0.001), pTNM stage (P = 0.001), and positivity for FCCs. After adjusting for covariates, patients with positive FCCs had lower progression-free survival than patients with negative FCCs. Conclusion The ISET platform highly enriched nucleated cells from peritoneal lavage fluid, and indicators comprising EpCAM, CEP8, and CEP17 confirmed the diagnosis of FCCs. As a potential detection method, it offers an opportunity for early intervention of OPM and an extension of patient survival.
Keywords: Isolation by size of epithelial tumor cells (ISET); Peritoneal metastasis; Gastric cancer; Free cancer cells; Prognosis; Occult peritoneal metastasis